Creative Process and Multivariate Factors through a Creative Course “Keep Calm and Be Creative” - Aleksandra Vuichard; Marion Botella; Isabelle Capron Puozzo (Journal of Intelligence, 2023)
Creativity has been studied for a long time and it has become a more significant topic of research in educational fields in recent decades. The present paper outlines a multivariate approach to creativity and substantiates this approach by investigating the creative process and multivariate factors through a creative course for master’s students at the University of Teacher Education in Switzerland. Our goal is to examine more specifically the stages of the creative process and the emerging multivariate factors in different creative activities. The article reports findings from the analysis of students’ creative report process diaries as well as semi-structured interviews. Drawing on experiential learning, this pilot study was conducted in collaboration with master’s student teachers (n = 10). The results show that the different microlevels of the creative process are the subject of variations from one creative experience to another. Most factors of the multivariate approach emerge from this kind of creative training. The discussion will allow for a review of the research results and also a better understanding of the creative process in the pedagogy of creativity.